Two high-risk susceptibility loci at 6p25.3 and 14q32.13 for Waldenström macroglobulinemia - McMaster, Mary L; Berndt, Sonja I; Zhang, Jianqing; Slager, Susan L; Li, Shengchao Alfred; Vajdic, Claire M; Smedby, Karin E; Yan, Huihuang; Birmann, Brenda M; Brown, Elizabeth E; Smith, Alex; Kleinstern, Geffen; et al. (Nature communications, 2018)
Waldenström macroglobulinemia (WM)/lymphoplasmacytic lymphoma (LPL) is a rare, chronic B-cell lymphoma with high heritability. We conduct a two-stage genome-wide association study of WM/LPL in 530 unrelated cases and 4362 controls of European ancestry and identify two high-risk loci associated with WM/LPL at 6p25.3 (rs116446171, near EXOC2 and IRF4; OR = 21.14, 95% CI: 14.40-31.03, P = 1.36 × 10-54) and 14q32.13 (rs117410836, near TCL1; OR = 4.90, 95% CI: 3.45-6.96, P = 8.75 × 10-19). Both risk alleles are observed at a low frequency among controls (~2-3%) and occur in excess in affected cases within families. In silico data suggest that rs116446171 may have functional importance, and in functional studies, we demonstrate increased reporter transcription and proliferation in cells transduced with the 6p25.3 risk allele. Although further studies are needed to fully elucidate underlying biological mechanisms, together these loci explain 4% of the familial risk and provide insights into genetic susceptibility to this malignancy.
Keywords: lidské chromozomy, pár 14; Waldenstrom Macroglobulinemia; Base Sequence; Chromosomes, Human, Pair 14; zelené fluorescenční proteiny; typy dědičnosti; genotypizační techniky; genetická predispozice k nemoci; Inheritance Patterns; MicroRNAs; Genes, Reporter; Waldenströmova makroglobulinemie; lidé; mikro RNA; Risk Factors; HEK293 buňky; Genotyping Techniques; Reproducibility of Results; anotace sekvence; Genetic Predisposition to Disease; reprodukovatelnost výsledků; lidské chromozomy, pár 6; jednonukleotidový polymorfismus; Polymorphism, Single Nucleotide; Family; HEK293 Cells; Cell Proliferation; Green Fluorescent Proteins; proliferace buněk; Molecular Sequence Annotation; rodina; Humans; rizikové faktory; Chromosomes, Human, Pair 6; sekvence nukleotidů; reportérové geny